Kinetic and kinematic synchronization between blind and guide sprinters - Nagahara, R. (Journal of Sports Sciences, 2021)
This study aimed to evaluate the magnitude of synchronization and symmetry between blind and guide sprinters. Elite and sub-elite pairs of male blind sprinters and guide sprinters performed maximal effort 60-m sprints, during which ground reaction force (GRF) for a 50-m distance and sprinting motion during the initial acceleration and maximal speed phases were measured. While there were no significant differences in spatiotemporal and GRF variables between the sprinters of the elite pair, flight time and braking, propulsive and vertical forces in the sub-elite pair showed a significant difference between the sprinters. During the initial acceleration phase, although thigh segment angles in the sagittal plane between the blind and guide sprinters showed obvious phase shifting (lag = -0.078 and -0.088) for the sub-elite pair, the elite pair showed no phase shift and high cross-correlation coefficients (0.96 and 0.83) for the corresponding variable. During the maximal speed phase, for both the elite and sub-elite pairs, there were trivial lags (-0.004 to 0.008) and high cross-correlation coefficients (>0.98) between the thighs of the blind and guide sprinters for both legs. The results demonstrate that a higher magnitude of synchronization between blind and guide sprinters is possibly important for better blind sprint performance.